PENGARUH JENIS MULSA DAN PUPUK GANDASIL-B TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsium frustescens L.) PADA TANAH GAMBUT PEDALAMAN (The Effect of Mulch Type and Gandasil-B Fertilizer on The Growth and Yield of Chili Pepper (Capsicum frutescens L.) on Inland Peat Soil) - noto, Ri; Winarti,, S.; lampak, Sa (Universitas Palangka Raya, 2017)
ABSTRACTThis research was aimed to investigate the effect of mulch type and gandasil-B fertilizer on thegrowth and yield of chili pepper (Capsicum frutescens L.) on inland peat soil. The method usedin this research was two-factor Randomized Block Design with split plot arrangement and threereplications. The main plot was the mulch type which consists of three treatments, namely:control, cogon grass and silver-black plastic mulch, and as sub plot was the dose of gandasil-Bwhich consists of four 4 levels, namely: 0, 1, 2, and 3 g L-1 water. Results showed that theinteraction between different types of mulch and gandasil-B fertilizer only had significant effecton the diameter of the stem, the number of productive branch, the number of fruit per plant, andthe weight of fruit per plant. The utilization of silver-black plastic mulch and gandasil-B fertilizer at the concentration of 3 g L-1 water showed more number of productive branch(14.00 branches) and number of fruit (151.17 fruits) per plant and the weight of fruit(166.52 g) per plant was significantly higher.Keywords : Mulch, cogon grass, silver-black plastic, Gandasil-B, inland peat soil